2020
DOI: 10.1038/s41598-020-72765-2
|View full text |Cite
|
Sign up to set email alerts
|

Low rather than high mean corpuscular volume is associated with mortality in Japanese patients under hemodialysis

Abstract: Recent studies have reported that high mean corpuscular volume (MCV) might be associated with mortality in patients with advanced chronic kidney disease (CKD). However, the question of whether a high MCV confers a risk for mortality in Japanese patients remains unclear. We conducted a longitudinal analysis of a cohort of 8571 patients using data derived from the Japan Dialysis Outcomes and Practice Patterns Study (J-DOPPS) phases 1 to 5. Associations of all-cause mortality, vascular events, and hospitalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…MCH refers to the amount of hemoglobin per erythrocyte, and low-level MCH has been found to be strongly associated with intensive care admission due to myocardial infarction (17). In a study, low level MCH was found to be highly correlated with mortality rate, and a significant relationship was pointed out between very high level of MCH and mortality (18). In our study, in terms of the CBC analysis, there was no significant difference in hemoglobin and hematocrit levels between the two groups, but it was found that MCH increased significantly in the study group (p=0.03).…”
Section: Discussionmentioning
confidence: 99%
“…MCH refers to the amount of hemoglobin per erythrocyte, and low-level MCH has been found to be strongly associated with intensive care admission due to myocardial infarction (17). In a study, low level MCH was found to be highly correlated with mortality rate, and a significant relationship was pointed out between very high level of MCH and mortality (18). In our study, in terms of the CBC analysis, there was no significant difference in hemoglobin and hematocrit levels between the two groups, but it was found that MCH increased significantly in the study group (p=0.03).…”
Section: Discussionmentioning
confidence: 99%
“…This is inconsistent with the results obtained in the general population by Vezzoli et al (15) . This can be explained by the fact that low red cell indices are very common in CKD patients and they result mainly from chronic inflammation and insufficiency of iron (16) . The reduced levels of MCV and MCH are closely related to the deficiency of Klotho (17) .…”
Section: Discussionmentioning
confidence: 99%
“…21 A larger cohort study including 109,501 incident HD patients showed MCV > 100 fl was associated with both CV and infectious mortality. 9 However, Sun et al 22 and Honda et al 10 reported a low MCV to be a risk factor for poor survival in patients receiving elective percutaneous coronary intervention and HD. In this study, we found HD patients with an elevated RDW and MCV level were suffered with a higher risk for all-cause mortality in an unadjusted model.…”
Section: The Effect Of Interaction Between Rdw and MCV On All-cause A...mentioning
confidence: 99%
“…9 However, another longitudinal analysis drew a conclusion that lower level of MCV was significantly associated with a higher incidence of all-cause mortality in HD patients. 10 Although the variability in RBC size seems to be novel risk factors for poor prognosis, the relationship between MCV and mortality is still controversial. And we would like to definie the effect of the combination of RDW and MCV on mortality in maintenance HD patients in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation